Processing and final properties improvement of polyolefin-sepiolite and carbon nanofibre nanocomposites - La Tegola, S. (2011)
In this work polypropylene (PP) nanocomposites with different nanofillers (sepiolites and carbon nanofibres) have been produced, processed by injection moulding and fibre spinning and analyzed in terms of mechanical properties improvements. Different concentrations of both fillers were used in nanocomposites preparation. The influence of nanofiller type and amount on mechanical properties were analyzed and discussed for each process studied. This study was completed with a basic morphological characterization in order analyze the nanofiller dispersion, distribution and orientation in the nanocomposites. The results achieved show that it is possible to obtain a good dispersion and distribution of the each kind of nanofillers with conventional processing methodologies when the nanofiller concentration is small. Moreover the nanocomposites obtained had better properties than the starting polymers, showing that sepiolite and carbon nanofiller are able to provide an important contribution to the improvement of mechanical properties of the materials analyzed, enlarging the final application possibilities of PP based products.